2010
DOI: 10.1111/j.1469-185x.2010.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of female mating status using chemical signals and cues

Abstract: Males of many species choose their mate according to the female's reproductive status, and there is now increasing evidence that male fitness can depend on this discrimination. However, females will also aim to regulate their mating activity so as to maximize their own fitness. As such, both sexes may attempt to dictate the frequency and timing of female mating, reflecting the potentially different costs of female signaling to both sexes. Here, I review evidence that chemical cues and signals are used widely b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
114
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(115 citation statements)
references
References 130 publications
0
114
0
1
Order By: Relevance
“…However, almond moth females are considered mostly monandrous (McNamara et al, 2008) and, therefore, age-related mate selection would be effective only if high proportions of old females were unmated, which is unlikely. Males may also be capable of assessing the mating status of females through differences in female chemical signals (Thomas, 2011). For monandrous moth species, such as the almond moth, this is somewhat trivial, as sex pheromone production is probably permanently shut down in mated females (e.g., Foster, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…However, almond moth females are considered mostly monandrous (McNamara et al, 2008) and, therefore, age-related mate selection would be effective only if high proportions of old females were unmated, which is unlikely. Males may also be capable of assessing the mating status of females through differences in female chemical signals (Thomas, 2011). For monandrous moth species, such as the almond moth, this is somewhat trivial, as sex pheromone production is probably permanently shut down in mated females (e.g., Foster, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Although the original function of cuticular hydrocarbons is thought to be protection against desiccation, it is now widely accepted that these chemicals are also used in short-range communication [11]. In females, changes in cuticular hydrocarbons have been widely reported, with mated females more often than not displaying a significantly different cuticular hydrocarbon profile than their unmated counterparts [12]. In males, it has recently been demonstrated that the social environment can influence the expression of cuticular hydrocarbons [13], and that changes in cuticular hydrocarbon expression can occur rapidly [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, most sex pheromones in spiders are contact chemicals associated with the web or draglines released by females during locomotion (Huber 2005;Gaskett 2007;Schulz 2013). Although many studies have shown that males generally prefer the silk from virgin females over those from immature and/or mated females Roberts and Uetz 2005;Stoltz et al 2007;Uetz and Norton 2007;Costa 2010, 2014;Thomas 2011;Tuni and Berger-Tal 2012), relatively less is known about whether male spiders are able to discriminate silk cues from virgin females varying in postmaturation ages (but see Roberts and Uetz 2005;Shamble et al 2009;Costa 2010, 2014;Klein et al 2012). From a male's perspective, chemical advertisement of the female receptivity may not minimize its searching costs by avoiding unavailable mates, but may reduce its risk of being cannibalized.…”
Section: Introductionmentioning
confidence: 99%